2020
DOI: 10.3389/fevo.2020.00070
|View full text |Cite
|
Sign up to set email alerts
|

Perianth Phyllotaxis Is Polymorphic in the Basal Eudicot Anemone and Eranthis Species

Abstract: We thank the Kuwagata family, S. Maeda and K. Horibe for their support in field work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
(68 reference statements)
0
4
0
Order By: Relevance
“…The appearance of mature flowers and their development can differ, exemplified by rapid spiral initiation in calyx whorls in core eudicot species (Endress and Doyle 2007 ). Mathematical modelling studies have shown that the post-meristematic modification of an organ by repulsive interaction between organs enables concentric arrangement following spiral initiation and stabilizes the organ number in each circle (Kitazawa and Fujimoto 2015 , 2020 ). This result suggests that interaction among organs, which is affected by the determinate nature of flowers and the growth control of each organ, can be crucial to ensure robust organ positioning.…”
Section: Floral Phyllotaxis and Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The appearance of mature flowers and their development can differ, exemplified by rapid spiral initiation in calyx whorls in core eudicot species (Endress and Doyle 2007 ). Mathematical modelling studies have shown that the post-meristematic modification of an organ by repulsive interaction between organs enables concentric arrangement following spiral initiation and stabilizes the organ number in each circle (Kitazawa and Fujimoto 2015 , 2020 ). This result suggests that interaction among organs, which is affected by the determinate nature of flowers and the growth control of each organ, can be crucial to ensure robust organ positioning.…”
Section: Floral Phyllotaxis and Developmentmentioning
confidence: 99%
“…Another perspective, not considered in the approach of Sauquet et al ( 2017 ), is the coexistence of multiple states and the possibility that the ancestral state is polymorphic (Sauquet et al 2018 ). Recently, we reported the coexistence of spirals and whorls in the perianth phyllotaxis at maturity in Anemone and Eranthis (Ranunculaceae) flowers (Kitazawa and Fujimoto 2020 ). Studies on phyllotaxis variations suggest that such variations are common in nature, and variable phenotypes can be generated from a single developmental system, with inevitable existence of stochasticity in biological processes.…”
Section: Floral Evo-devo and Stochasticitymentioning
confidence: 99%
“…Another character is the order of organ initiation. A third character (Kitazawa and Fujimoto, 2018;Fujimoto and Kitazawa, 2020) is the pattern of overlapping between margins of adjacent organs (aestivation). Quincuncial aestivation normally correlates with sequential sepal initiation in angiosperms.…”
Section: Resultsmentioning
confidence: 99%
“…Exterior tepals are typically initiated earlier during the floral development in many clades of plant species, including Anemone and Arabidopsis (Smyth et al, 1990;Ren et al, 2010). At present, tepal arrangements are identified manually (Endress, 2010;Ronse De Craene, 2010;Vislobokov et al, 2014;Kitazawa and Fujimoto, 2018;Kitazawa and Fujimoto, 2020). The visual examination of a large number of flower images is extremely labor intensive; moreover, judging these images unless one is a specialist is difficult.…”
Section: Introductionmentioning
confidence: 99%